On the limit theorems for the random functions. I - Statulevičius, V. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Статулявичус. О предельных теоремах для случайных функций. IV. Statulevičius. Atsitiktinių funkcijų ribinių teoremų klausimu. I